Posturography examination as a diagnostic tool in children - a review of the literature - Borek, Joanna Monika; Malak, Roksana Ewa; Matthews-Brzozowska, Teresa; Samborski, Włodzimierz (Journal of Medical Science, 2019)
Introduction. Posturograph tests are used to assess the vestibular reflex, which can be helpful for specialists who analyze body balance disorders. Despite many studies on the stability of body posture in pediatric patients, there is still a lack of reliable analysis.Aim. Performing a review of the literature to verify the relationship between balance and body posture as well as stomatognathic system as a part of motor system and the craniofacial complex using a posturograph.Material and Methods. A review of the literature has been carried out for the posturographic examination as a diagnostic tool. The following work is for reference only. A review of the Google Schoolar database and PubMed was made. Keywords used in the search are: (children) and (posturography, posture control, balance, temporomandibular joint). The authors took into account reports published in Polish and English. For the purposes of this review, strict criteria for the inclusion and exclusion of research work have been created.Results. The authors analyzed 335 research papers, of which 5 articles were qualified after the analysis. Studies show that there is a relationship between posturographic examination and postural disorders in children. However, the results are not conclusive and further research is necessary before these results can be considered as fully generalized.Summary. It is necessary to standardize the research using a posturograph. There is a need for further research due to the lack of standardized measurements showing norms for individual age groups.
Keywords: children; posturography; postural control; balance; temporomandibular joint